2011
DOI: 10.1182/blood-2011-03-341214
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1 drives annexin A2 system-mediated perivascular fibrin clearance in oxygen-induced retinopathy in mice

Abstract: Oxygen-induced retinopathy (OIR) is a well-characterized model for retinopathy of prematurity, a disorder that results from rapid microvascular proliferation after exposure of the retina to high oxygen levels. Here, we report that the proliferative phase of OIR requires transcriptional induction of the annexin A2 (A2) gene through the direct action of the hypoxiainducible factor-1 complex. We show, in addition, that A2 stabilizes its binding partner, p11, and promotes OIR-related angiogenesis by enabling clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 50 publications
4
69
0
Order By: Relevance
“…This effect was specific to Kv1.3 channels (the protein levels of SK2, a K Ca channel expressed in Jurkat T cells, were unchanged) and to the Kv1.3 pore forming ␣ subunit (the expression of the auxiliary Kv␤2 subunit was unchanged) (5). Herein we showed that the decrease in Kv1.3 surface expression during hypoxia is also specific of this membrane protein because, in accordance with previous studies, the expression of the plasma membrane protein cadherin remained unaltered (26,27).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This effect was specific to Kv1.3 channels (the protein levels of SK2, a K Ca channel expressed in Jurkat T cells, were unchanged) and to the Kv1.3 pore forming ␣ subunit (the expression of the auxiliary Kv␤2 subunit was unchanged) (5). Herein we showed that the decrease in Kv1.3 surface expression during hypoxia is also specific of this membrane protein because, in accordance with previous studies, the expression of the plasma membrane protein cadherin remained unaltered (26,27).…”
Section: Discussionsupporting
confidence: 91%
“…The effect of hypoxia on Kv1.3 surface expression was compared with that on the plasma membrane protein cadherin (26,27). We found no effect of hypoxia on cadherin.…”
Section: Prolonged Exposure To Hypoxia Decreases Kv13 Surfacementioning
confidence: 73%
“…This comprises matrigel implant, corneal pocket and oxygen-induced retinopathy, the latter mimicking aspects of diabetic retinopathy (Ling et al, 2004;Huang et al, 2011;Hedhli et al, 2012).…”
Section: Anxa2 Ko Micementioning
confidence: 99%
“…It can exist as a monomer or as heterotetrameric complexes with the S100A10 protein, which enhances its membrane phospholipid binding affinity. In our hands, the highest expression of annexin A2 observed at the cell surface was achieved by placing cells under hypoxia, probably because it combines both membrane translocation and an increase in annexin A2 gene expression, which has been shown to be dependent on HIF-1 (23). Cellular reoxygenation after hypoxia is followed by ROS burst, and inhibiting ROS production using antioxidant NAC decreased stress-induced annexin A2 surface expression.…”
Section: Discussionmentioning
confidence: 65%
“…Second, despite the absence of a transmembrane domain, intracellular annexin A2 can swiftly translocate to cell surface upon stress signals (25) in agreement with the increase of FMS-01 binding on glioblastoma cells treated for only 30 min at 42°C. In endothelial cells, annexin A2 translocation is obtained, in vitro but also in vivo, within minutes in response to heat stress, thrombin exposure, or hypoxia and relies on annexin A2 phosphorylation (21)(22)(23). Third, consistent with γδ T-cell responses to tissue injury (26) annexin A2 plays a role in membrane repair and wound healing (27), which is supposedly because of an intracellular rise in Ca 2+ upon membrane damage (28).…”
Section: Discussionmentioning
confidence: 97%